On the roles of genes encoding methionine-rich proteins in Arabidopsis thaliana in response to abiotic stresses - Ha, Chu Duc; Ngoc Quynh, Le Thi; Ly Thu, Pham Thi; Huy, Nguyen Quang; Dung, Le Tien (Academia Journal of Biology, 2015)
Methionine (Met) is an essential amino acid, which plays an important role in the plant cells. Oxidation of Met residues in proteins caused by abiotic stresses can lead to damages in cellular components, which may further affect metabolism, signal transduction in the cell and consequently the viability of organisms. In this study, 121 genes encoding Met-rich proteins (MRP) were identified from Arabidopsis thaliana database. Gene ontology analysis showed that the cellular functions of half of these genes are yet be known. Based on their transcript levels under normal and stress conditions, we found that 23 and 16 AtMRP genes were induced and repressed more than 2-fold, respectively, under dehydration. On the other hand, 11 and 17 genes were induced and repressed more than 2-fold, respectively, under high salinity treatment. Of these, 10 AtMRP genes were transcriptionally responsive to both drought and high salinity. AT4G33467 was the most induced gene, its transcript level was up-regulated 337.5-fold by drought. Among stress-repressed genes, AT3G55240 was the most down-regulated gene, its transcript level was repressed by 60.3 and 26.9-fold under dehydration and high salinity treatments, respectively. The transgenic line RBC1, who overexpressed AT3G55240, was more sensitive to high salinity treatment than the wild type. Taken together, this is the first report on the involvement of genes encoding MRPs in the adaptation of plants to abiotic stresses.